Nozicks Theory of Justice A Critique of Rawlss Egalitarian Principles (Global Journal of Human-Social Science, 2025)
Nozick disagrees arguing that Rawls theory contradicts fundamental individual rights particularly the right to property For Nozick any state-enforced redistribution is an infringement on individual liberty He advocates for a minimal state whose sole mission is to protect these rights without interfering in the distribution of wealth which he believes should be left to market dynamics This analysis highlights the limitations of Nozick s view of justice which by rejecting any state intervention leads to increased social inequalities His approach aligns with a neoliberal logic that prioritizes individualism at the expense of social justice Thus a minimal state is ineffective since under the guise of defending freedom it actually perpetuates social imbalances
Keywords: individual rights; justice; liberty; minimal state; socials inequalities; redistribution